Effects of 910 MHz Solid-State Microwave Cooking on the Quality Properties of Broccoli (Brassica olearacea L. var. Italica Plenck), Carrots (Daucus carota subsp. Sativus), and Red Peppers (Capsicum annuum L. cv. Kapya) - Gönül Çavuşoğlu Kaplan; Ebru Fıratlıgil (Foods)
Domestic microwave ovens offer rapid cooking but face challenges such as non-uniform temperature distribution and hot spots. A novel solid-state heating system, which precisely controls microwave frequency and power, provides a promising alternative to traditional microwave ovens utilizing magnetron systems. This study compared the effects of solid-state microwave cooking on the quality of broccoli, red peppers, and carrots with those of traditional microwave and conventional cooking. The traditional microwave cooking used in this study operated at 2450 MHz, while the solid-state system functioned between 902 and 928 MHz. Weight loss was highest for conventional cooking, reaching a maximum of 34%, whereas microwave cooking resulted in a maximum of 11.65% and solid-state microwave cooking in 17.04%. The total phenolic content obtained through conventional cooking ranged between 61.58 and 116.51 mg GAE (gallic acid equivalents)/100 g dry basis, while microwave cooking resulted in a range of 88.04–110.92 mg, and solid-state microwave cooking achieved values between 76.14 and 122.91 mg. Furthermore, reductions in chlorophyll content were observed to be 68.2%, 25.6%, and 35.7% for conventional, microwave, and solid-state microwave cooking, respectively. Lycopene content after conventional cooking decreased to 224.73 mg/100 g dry basis, compared to 289.55 mg after microwave cooking and 242.94 mg after solid-state microwave cooking. β-carotene content showed a decrease of 14.5% in conventional cooking, while both microwave methods showed an increase of 14.7%. These results suggest that solid-state microwave cooking may have promising positive effects on food quality.